The role of e-Government in overcoming the consequences of the COVID-19 pandemic in Nigeria - Henry Chima Ukwuoma; Nimfel Elisha Cirman; Peter Olorunleke Oye (Goodwood Publishing, 2022)
Purpose: The article aims at identifying the challenges of e-government amid the COVID-19 pandemic in Nigeria and proffered recommendations to arrest the identified challenges. This paper also examined e-Governance in selected countries such as the United States of America, the United Kingdom, and Canada and how it has fared including Nigeria revealing its implications for Nigeria as a developing nation. Research Methodology: The article adopts a review study approach in analyzing the subject. Results: Some of the challenges identified by the study include but are not limited to inadequate technical know-how and ICT skills to drive and sustain e-government. Recommendations from the study include, the Ministry of Communications Technology and Digital Economy to build a backbone that will connect all States of the country and the upskilling of the workforce through the Ministry of Labour and Employment amongst others. Limitations: Insufficient quantitative data based on the subject under discourse Contributions: Identified possible areas that the Nigerian government could look into to improve e-government in order to promote inclusivity, awareness, and most importantly reduce the cost of governance.